2022
DOI: 10.3390/w14223779
|View full text |Cite
|
Sign up to set email alerts
|

Flood Analysis Using HEC-RAS and HEC-HMS: A Case Study of Khazir River (Middle East—Northern Iraq)

Abstract: Floods frequently threaten villages near the Khazir River’s floodplains, causing crop losses and threatening residential areas. We used flood-related hydrological software, including WMS and HEC-HMS, to study this issue and determine how to reduce the recurrence of flooding. The software can be used to calculate a hydrograph of torrential flows in a river drainage basin and estimate the volume of torrential water and its flow rates on the Earth’s surface. The depth of rain has been evaluated and calculated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Several studies have revealed that Iraq, including HQW, has undergone devastating floods and drought episodes in recent years [10,59,[115][116][117][118]. However, despite receiving a substantial volume of precipitation, the surface water in HQW has not been adequately exploited due to a lack of runoff harvesting structures (e.g., dams), where most runoff waters are lost to drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that Iraq, including HQW, has undergone devastating floods and drought episodes in recent years [10,59,[115][116][117][118]. However, despite receiving a substantial volume of precipitation, the surface water in HQW has not been adequately exploited due to a lack of runoff harvesting structures (e.g., dams), where most runoff waters are lost to drainage.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation is carried out utilizing the HEC-HMS software, which was developed by the Center for Hydrological Engineering in collaboration with the US Army Corps of Engineers. This software has been widely employed in various hydrological research endeavors and is designed to replicate rainfallrunoff processes in diverse geographical areas, encompassing floods, water resources, and both small and large river basins, as well as urban and natural runoff from watersheds [6]. Applying the SCS Unit Hydrograph method, this study aims to establish a model of watershed characteristics, including soil type, vegetation cover, and land usage, and the corresponding runoff curve numbers.…”
Section: Methodsmentioning
confidence: 99%
“…It is also important to discuss applications of other hydrological models that have similar functionalities as SWAT model. There will be two models presented: HEC-HMS and HEC-RAS model [23][24][25][26]. HEC-HMS is a hydrologic modelling program that allows to establish rainfall-runoff relationships based on watershed characteristics.…”
Section: Methodsmentioning
confidence: 99%